Respon Tanaman Selada Merah (Lactuca Sativa L.) Terhadap Larutan Hara (AB Mix ) Pada Instalasi Horizontal Sistem Hidroponik - Satriawan, Dedi; Aprillia, Dwi Resti (Universitas Bengkulu, 2019)
This study aims to determine the response given by the red lettuce plant to the provision of nutrients in the form of nutrient solution (AB Mix) on the horizontal installation of the hydroponic system. The study was conducted on December 20, 2017 until February 16, 2018 at the PKK Gardens Education Center in Bengkulu province. Seeding process of Red Lettuce Seedlings is carried out for 14 days then transferred to a net pot at the installation in the Greenhouse. Fertilizers with the Fiora A and B Brands are dissolved to be mixed in a nutrient bath with a capacity of 3000 L with a nutrient density of 500 ppm in the Greenhouse to be distributed to the horizontal installation of the hydroponic system inside the Greenhouse. Then growth observations were carried out on 10 plant samples with parameters of leaf length, leaf width, number of leaves, stem height, andstem diameter for 30 days. The results obtained by sample 1-10 have an average growth and development that is not much different. The maximum leaf length and leaf width parameters are in samples 2 and 3. While the highest number of leaf strands in sample 3 is 22 strands with an average of 18 strands and sample 4 has the highest stem height parameter of 3.5 cm with an average height 2.7 cm. The largest stem diameter in sample 4 is 4.1 cm with an average of 3.38 cm. The response of red lettuce after the last week showed symptoms of leaves that are less red with relatively more withered body.